Modeling sepsis, with a special focus on large animal models of porcine peritonitis and bacteremia - Vintrych, Pavel; Al-Obeidallah, Mahmoud; Horák, Jan; Chvojka, Jiří; Valešová, Lenka; Nalos, Lukáš; Jarkovská, Dagmar; Matějovič, Martin; Štengl, Milan (Frontiers in Physiology, 2023)
Infectious diseases, which often result in deadly sepsis or septic shock, represent a major global health problem. For understanding the pathophysiology of sepsis and developing new treatment strategies, reliable and clinically relevant animal models of the disease are necessary. In this review, two large animal (porcine) models of sepsis induced by either peritonitis or bacteremia are introduced and their strong and weak points are discussed in the context of clinical relevance and other animal models of sepsis, with a special focus on cardiovascular and immune systems, experimental design, and monitoring. Especially for testing new therapeutic strategies, the large animal (porcine) models represent a more clinically relevant alternative to small animal models, and the findings obtained in small animal (transgenic) models should be verified in these clinically relevant large animal models before translation to the clinical level.